Assessment of dust exposure and chronic respiratory symptoms among workers in medium scale woodwork factories in Ethiopia; a cross sectional study - Awoke, Tegegnework Yitayew (BMC Public Health, 2021)
BACKGROUND: Wood dust in a form of inhalable particulates can penetrate the lung tissues and affect respiratory health. Woodwork factory workers are at a greater risk of developing respiratory health problems because of exposure in their working environment, but existing data were few. The aim of this study was to assess the prevalence of chronic respiratory symptoms, associated factors, and concentration of personal total wood dust level among medium-scale woodwork factory workers. METHODS: An institutional based cross-sectional study was conducted among 506 woodwork factory workers. We selected study participants using a simple random sampling technique. We assessed chronic respiratory symptoms using the British Medical Research Council respiratory symptoms questionnaire with a few modifications. A multivariate logistic regression model was used to identify the factors. Forty dust measurements were collected from 20 randomly selected workers using a closed-face cassette (CFC) personal sampler. We analyzed the dust samples gravimetrically using a standard microbalance scale. RESULTS: We recruited a random sample of 506 workers in the study with a response rate of 98%. The prevalence of chronic respiratory health symptoms among woodworkers was 69.8% with a prevalence of cough (54.6%), phlegm (52.2%), wheezing (44.6%), breathlessness (42.1%), and chest pain (42.9%). Past occupational dust exposure history (AOR = 2.09, 95% CI; 1.09–4.01), work experience > 5 years (AOR = 9.18, 95% CI; 5.27–16.00), using bio-fuel as energy for cooking (AOR = 2.42, 95% CI; 1.44–4.07), and having no occupational safety and health training (AOR = 3.38, 95% CI; 1.20–9.49) were factors that significantly associated with chronic respiratory symptoms among woodwork workers. The geometric mean (GM) of dust exposure level among woodworkers was 10.27 mg/m(3), which exceeded the limit of 10 mg/m(3) set by the ACGIH. CONCLUSIONS: High prevalence of chronic respiratory symptoms was reported from woodwork factory workers. Increased work- experience, using bio-fuel as an energy source for cooking, past occupational dust exposure history, and having no occupational safety and health training were identified risk factors. The measured average personal wood dust exposure level was above the recommended occupational threshold limit value. Therefore, workers’ wood dust exposure reduction and control methods and respiratory health awareness programs should be implemented.